On an optimal robust digital image watermarking based on SVD using differential evolution algorithm - Ling, Huo-Chong; Phan, Raphael C.-W.; Heng, Swee-Huay (2011)
It is shown that the optimal robust digital image watermarking based on singular value decomposition using differential evolution algorithm proposed by Veysel Aslantas [Opt. Commun. 282(5):769-777 (2009)] has a serious fundamental flaw and should not be used for proof of ownership application. (C) 2011 Elsevier B.V. All rights reserved